PENGGUNAAN GAME ANAGRAM MANIA DALAM PENINGKATAN HASIL BELAJAR BAHASA INDONESIA MATERI KATA KERJA KELAS III SD NEGERI 3 JANGKA - Alhusna; Nurlaili; Zulkarnaini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low learning outcomes of Indonesian language on the material of verbs of third-grade students of SD Negeri 3 Jangka. Based on the results of initial observations and pre-action tests, most students have difficulty in understanding and using verbs, which has an impact on the low achievement of learning outcomes. This study aims to describe the improvement in learning outcomes, analyze teacher and student activities, and determine the responses of third-grade students of SD Negeri 3 Jangka to the material of verbs through the use of innovative media Anagram Mania Game based on the Wordwall platform. This study uses a qualitative approach with the type of Classroom Action Research (CAR) which is implemented in two cycles. The subjects of the study were 20 third-grade students of SD Negeri 3 Jangka in the 2026/2027 academic year. Data collection techniques used include tests, observations, and interviews. Data were analyzed through calculating the percentage of learning completeness, teacher and student activities, and analysis of student responses. The results of the study showed an increase in learning outcomes of Indonesian language on the material of verbs, an increase in teacher and student activities and an increase in student responses, the percentage of classical completeness increased from 65% in cycle I to 80% in cycle II. In addition, teacher activity increased from 81.81% to 88.32% and student activity increased from 76.36% to 87.27%. The results of student interviews regarding the Anagram Mania Game gave a very positive response, feeling happy, and finding it easier to remember basic verb structures and affixes. Thus, learning using the Anagram Mania Game can improve the ability of Indonesian language learning outcomes regarding verb material.